Barriers to learning Dari literature among non-Persian language students of the Dari department of Jawzjan University - Radfar, Hussain (International Journal of Innovative Research and Scientific Studies, 2021)
This paper, which is written under the title "Barriers to learning Dari literature among non-Persian language students of the Dari department of Jawzjan University", contains challenges and solutions through which the problem of learning Dari literature among the students of this department can be identified and will be solved by the application of the solutions presented in this paper. The main purpose of this study is to identify the general and minor barriers that non-Persian language students of the Dari Department of Jawzjan University struggle with to learn better. Therefore, this research is very important, because so far, no research has been done in this field. The research method applied in this research is a descriptive-survey method. The population of this study was 67 students, and the sample size (n=57) was selected using Cochran's formula. SPSS software was used to analyze the data. Findings of the present study confirm the hypotheses such as the poor academic foundation of students, the unfamiliarity of teachers and students with modern teaching methods, lack of educational facilities, lack of motivation by families and teachers, and insufficient ability to the Dari language.